Animal welfare and environmental ethics - Rolston, Holmes, 1932-2025, author (Colorado State University. Libraries, 2021)
Bernard Rollin's main concerns are domestic and research animals. Tens of thousands of such animals have endured less suffering as a result of Rollin's seminal work. Animals are of moral concern because they have conscious interests, or telos. Rollin's use of telos is plausible though more specialized than usual. He develops an account of animal rights and has been influential in shaping legislation and regulations. Rollin has theoretical or in-principle ideals that are unlikely to be accepted as current practice. In result he adopts more moderate moral principles. In the fair-contract, husbandry dimension of agriculture, the farmer takes care of the cows and pigs, recognizing their rights, and then eats them, or sells them to be eaten. Environmental ethicists add that there are considerations in a more complex ethic, predation for example, that cannot be reached by conferring rights on them. Rollin has effectively analyzed the bioscience that confirms animal minds. He reaches a strange combination of kinship and chasm separating human and animal minds. Rollin's account of any deeper environmental ethics for a biospheric Earth is unsatisfactory, any respect for life beyond respect for sentience, especially his concepts of endangered species.
Animals: Mentality & Morals 2021 is a special publication arranged by the Colorado State University Department of Philosophy, during the failing health of Bernard E. Rollin and presented to him a few days before his death on November 19, 2021. The principal producer was Richard F. Kitchener. A small number of copies was printed, both hardbound and paper. There are seven contributors to the anthology. This anthology was first undertaken in 2016 but not published at that time. 129 pages. No ISBN found. Reprinted here is the Rolston contribution: "Animal Welfare and Environmental Ethics."
This Article was reprinted in the Journal of Applied Animal Ethics Research 2022, pages 1-17. May. https://brill.com/view/journals/jaae/jaae-overview.xml
Keywords: Rollin, Benard E.; veterinary medical ethics; animal ethics; animal rights; environmental ethics; telos